2019
DOI: 10.26479/2019.0502.81
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The excessive occurrence of heavy metals in natural loads has now-a-days become a matter of concern for the health of aquatic ecosystem. Heavy metals like Copper, Lead, Mercury, Cadmium, Nickel and Chromium are mainly responsible for water pollution. Metal pollution is a global problem growing at an alarming rate and aquatic organisms are continuously exposed to elevated levels of metals seriously threatening the whole ecosystem. The current experimental study of bioaccumulation of Copper, Lead and Cadmium in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In the present study, the bioaccumulation of chromium in the fish tissues were found in the order of liver > kidney> gill (Table 1) where as the bioaccumulation of nickel was found in the order of liver > kidney> gill(Table 3). A similar type of bioaccumulation trend was reported for cadmium in 30 days of exposure (Gandhewar and Zade, 2019). In the case of chromium exposed fish, even though the quantity of chromium accumulation in tissue was less in the case of gill when compared to liver and kidney, but the pattern of accumulation showed a continuously increasing trend until the 30 th day of exposure in all the tissues (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…In the present study, the bioaccumulation of chromium in the fish tissues were found in the order of liver > kidney> gill (Table 1) where as the bioaccumulation of nickel was found in the order of liver > kidney> gill(Table 3). A similar type of bioaccumulation trend was reported for cadmium in 30 days of exposure (Gandhewar and Zade, 2019). In the case of chromium exposed fish, even though the quantity of chromium accumulation in tissue was less in the case of gill when compared to liver and kidney, but the pattern of accumulation showed a continuously increasing trend until the 30 th day of exposure in all the tissues (Table 1).…”
Section: Resultssupporting
confidence: 77%